Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT Sodexo Sinergi Indonesia - Ghina Darmawan, Farras; Siska, Elmira; Indra, Natal (Institut Nalanda, 2023)
This research focuses on knowing the effect of compensation and the work environment on employee performance at PT Sodexo Synergy Indonesia. research used associative with a quantitative approach. The data collection technique uses saturated samples or non-probability sampling with a total sample of 54 respondents using a questionnaire. In processing data for analysis using SPSS 26.0 software tools which include data instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination tests. Based on the partial results of the study it was found that compensation has no significant effect on employee performance. However, work environment variables have a significant positive effect on employee performance at PT Sodexo Sinergi Indonesia. The compensation provided by the company is good so it does not have a detrimental impact on employee performance. Then, PT Sodexo Sinergi Indonesia has created a work environment that is good enough to support the work activities of its employees.